Maternal and child health and care provision in Palestine: data from the national electronic maternal and child health registry (MCH eRegistry). (March 2019) - Isbeih, Mervett; Venkateswaran, Mahima; Awwad, Tamara; Ghanem, Buthaina; Abu-Khader, Khadija; Hijaz, Taghreed; Baniode, Mohammad; Abbas, Eatimad; Salman, Rand; Ramlawi, Asad; Bogale, Binyam; Frøen, J Frederik
Abstract: Background: Good quality data from health systems can benefit several stakeholders, including policy makers, care providers, clients, and researchers. Conventional data collection methods for maternal and child health, such as household surveys, may not be suitable to assess processes of service delivery. The electronic maternal and child health registry (MCH eRegistry) has been implemented in 182 governmental primary care clinics in Palestine. Here we present the data in the MCH eRegistry. Methods: We processed the raw data in the MCH eRegistry from the West Bank, and documented validation rules for crude data points (time of entry, values allowed). Definitions and appropriate categorisations were created for core process indicators. Data from the MCH eRegistry and the electronic health information system in governmental hospitals were linked using statistical software. Findings: As per the second quarter of 2018, the MCH eRegistry contained raw data on 69 793 antenatal care visits, 27 304 postpartum care visits and 40 264 newborn care visits. From antenatal care, data on core process indicators were available for screening of anaemia (n=48 542), hypertension (n=66 814), diabetes (n=18 013), asymptomatic bacteriuria (n=31 757), as well as antenatal ultrasound (n=55 453). Distributions of raw data on haemoglobin and blood pressures had no extreme outliers. Links had been established between antenatal care and delivery data in governmental hospitals for 51% of births. Interpretation: The MCH eRegistry contains data from antenatal to postpartum and newborn care. These data have been successfully linked with delivery data, resulting in a large data set on continuity of care and birth outcomes. Furthermore, the data are accessible, of good quality, and can be used for studies of quality of care and maternal and newborn epidemiology, among others. Researchers are invited to use this resource in working towards improving the health system and the health of Palestinians. Funding: European Research Council and Research Council of Norway.